Implementasi Smart Identification Menggunakan Perangkat Smartphone dengan Raspberry PI (Studi Kasus : SMAN 2 Balikpapan) - Muhammad Alfarizi; Rakhmadhany Primananda; Reza Andria Siregar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Information Communication Technology (ICT) that is now supposed to be implemented to realize smart school needs more efficient services to achieve the transformation stage of change on ICT. Smart school is to optimize the technology used by students and schools to connect each other like attendance system which now no longer have to fill in written or manual signature. Therefore built smart identification system to integrate the server with mobile devices that students use by utilizing wireless technology. This Smart Identification will identify the mac address contained in the mobile device used by the students, as it will be more efficient for the attendance system that is only sufficiently connected with the access point with the result of stress test test using siege from 20 virtual users with elapsed time 59.65 second, average transaction rate 191.28 trans / sec, throughput 0.05 MB / sec, data transferred 2.98 Megabyte and percentage performance of Central Processing Unit ( CPU) in the range 85 to 95 percent but the system is still able to run well with no lag, system eror or failed transactions. Smart schools that support the smart identification system will be the basis of data user that will later be integrated into other systems.